Prophetic leadership model for today: an appraisal - Khaliq, Ahmad (Institute of Social Sciences & Development, Karachi-Pakistan, 2019)
The prophets of Islām in past have demonstrated Islamic attributes of a servant type leadership whereby a leader is servant first for his followers. The Islamic perspective to leadership is interesting, not because it is new, but because it worked in the past. For over 1,400 years from the time of Prophet Mohammad صلى الله عليه وسلم, Muslim leaders have demonstrated sound leadership and developed a great civilization in the process. This paper explores why an Islamic alternative might generate better outcomes. The assumption underlining this article is that the solutions of leadership crisis today are not only valid for Muslims, they tap into universal values and universal wisdoms and they are therefore valid for non-Muslims as well. It is our understanding that good leadership seems to be in short supply nowadays. Political, social and economic challenges dominate the headlines. The divide between the haves and the have not’s seems to be widening. The problem of how to make the today’s Millennium Development Goals (MDG), sustainable is becoming increasingly urgent. This is true in the Muslim world but it is increasingly true in developed countries as well. The recent electoral results in the UK and the United States indicate that what worked yesterday will be met by rising popular discontent by followers in the West and it will necessitate a change. Thus the qualities of Islamic leadership- teamwork, partnership, shura as a means of mutual consultation, and strategic thinking can ensure success and sustainable leadership.